Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $M,N\subset G$ be subgroups of an abelian group $G$ with $M\neq N$ and $M \cong N$ by an isomorphism $\phi: M\rightarrow N$.

I'm trying to show that there exists an automorphism $\psi$ of $G$ which extends $\phi$, i.e. $$ \psi(m) = \phi(m) \quad\forall m\in M. $$

I managed to proof the special case where $M+N=G$, as then each $g\in G$ can be uniquely written as $$g = m + n$$ where $m\in M$ and $n\in N$, and $$ \psi(m+n) := \phi(m) + \phi^{-1}(n) $$ has the requested properties (we even have $\psi(N)=M$).

In the general case, however, I cannot find a canonical choice for $\psi$ and I am unsure if the assertion is still true here actually, although it feels "right" and I could not come up with any counterexamples. Using an approach along the lines of the one above by writing $$g = g' + m + n$$ where $g'\in S:= G-(M+N)\cup \{0\}$ (or some similar subset of $G$), I don't get an unique representation as $S$ need not be a subgroup of $G$.

If anyone could give me a hint on how to proceed in the general case, or provide counterexamples or references, I would be grateful. Thanks.

share|cite|improve this question
up vote 5 down vote accepted

In general, it isn't true. Let $G=\mathbb Z/\left<2\right>\times \mathbb Z/\left<4\right>$. Then the subgroups generated by $(1,0)$ and $(0,2)$ are isomorphic, but the isomorphism cannot be extended to all of $G$ because there is an element $g\in G$ such that $g+g=(0,2)$, but there is no such element such that $g+g=(1,0)$

share|cite|improve this answer
That was helpful, thanks a lot. I should have tried harder finding a counterexample. – Andy Brandi Dec 18 '12 at 17:16

I think this is not true in general.

$G=\mathbb Z \,;\, M=2 \mathbb Z \,;\, N= 3\mathbb Z$

and $\phi(2x)=3x$. This cannot be extended, and this can be proven easely by contradiction (what can $\phi(1)$ be?).

share|cite|improve this answer
Ah, right. We would have $2\phi(1) = \phi(1) + \phi(1) = \phi(2) = 3$ which is a contradiction. Thanks! – Andy Brandi Dec 18 '12 at 17:16

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.